Will agroforests vanish? the case of damar agroforests in Indonesia - Kusters, K.; Ruíz Pérez, M.; Foresta, H. de; Dietz, T.; Ros-Tonen, M.A.F.; Belcher, B.; Manalu, P.; Nawir, A.A.; Wollenberg, Eva Karoline (2008)
Resin producing agroforestry in the Krui area of Sumatra in Indonesia is presented as an environmentally friendly, income generating land-use system which contributes to both development and conservation objectives. We studied the change in household income portfolios in three communities in the Krui area. The studies revealed that in the period 1995–2004 agroforestry remained the main source of income.We predict, however, that due to declining resin productivity per hectare, and rising price and demand for timber, an increasing number of farmers will cut their mature agroforests in the near future. At the same time our data suggests that farmers will continue tree planting activities. In result old agroforests may vanish while new ones will be established.